Analisis Rhodamin B pada Sample Lipstik dengan Metode Spektrofotometri UV-VIS - Ermi Abriyani; Annida Lutfiyah; Annisa Fitriyani; Kartika Sari; Maulida Mutiah A (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Many women use cosmetics to beautify themselves, one of which is using lipstick to add color to the lips so that they look fresher. To get attractive colors so as to increase consumer purchasing power, many lipstick makers use hazardous chemical compounds, one of which is Rhodamin B, which is a basic coloring agent in textiles and paper but is often misused in cosmetic preparations. Rhodamin B is a synthetic dye in the form of a crystalline powder, green or reddish purplein color, odorless, and fluoresce bright red in solution. The use of Rhodamin B in Europe has been banned as it is a strong carcinogen. Another negative impact is causing liver dyfunction or even triggering liver cancer. Conducted a review of various research journals that discussed the Rhodamin B dye in lipstick in 30 journals.